2009
DOI: 10.4314/wajae.v9i1.45661
|View full text |Cite
|
Sign up to set email alerts
|

Acute toxic effects of deltamethrin on tilapia, <i>Oreochromis niloticus</i> (Linnaeus, 1758)

Abstract: The effect of toxic compounds are variable among living organisms in different habitats. Toxicity tests are conducted to measure the effects of different pollutants on one or more species of organisms and in the form of LC 50s , assist in the development and application of water quality criteria for the protection of the aquatic environment. Active tilapia, Oreochromis niloticus, samples with size ranging between 4 and 6 cm standard length were exposed to different concentrations (between 0 and 30 µg/l) of Del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
2
6
0
1
Order By: Relevance
“…In addition more sensitive fishes in these aquatic habitats, if not tilapia, too would become easy victims of Trebon ® at these very low concentrations. More or less similar results have also been recorded by Yameogo et al (2001), Boateng et al (2006), Coimbra et al (2007), Al-Kahtani (2011) and Davoodi and Abdi (2012). Ali and Rani (2008) showed that the increase in exposure period decreases the LC50 value.…”
Section: Discussionsupporting
confidence: 71%
“…In addition more sensitive fishes in these aquatic habitats, if not tilapia, too would become easy victims of Trebon ® at these very low concentrations. More or less similar results have also been recorded by Yameogo et al (2001), Boateng et al (2006), Coimbra et al (2007), Al-Kahtani (2011) and Davoodi and Abdi (2012). Ali and Rani (2008) showed that the increase in exposure period decreases the LC50 value.…”
Section: Discussionsupporting
confidence: 71%
“…Mestres and Mestres (1992) report the 96-h LC 50 values in fish as follows: Salmo gairdneri, 0.39 mg/l; Cyprinus carpio, 1.84 mg/l; and Sarotherodon mossambica, 3.50 mg/l (Mestres and Mestres, 1996). The LC 50 value of deltamethrin in tilapia, Oreochromis niloticus was 15.47 mg/l as reported by Boateng et al (2006). Although deltamethrin is thought to be less toxic in field conditions due to its adsorption to sediments, these data are useful to assess the potential ecosystem risks (Viran et al, 2003).…”
Section: R E T R a C T E Dmentioning
confidence: 60%
“…The LC 50 of triazophos for 96 h treatment period in different fish species are as follows: 0.008 mg/L for Peseudorasobora parva , 0.035 mg/L for Tilapia nilotica , 0.060 mg/L for Colossoma brachypomum [ 23 ] and1.05 mg/L for Cirrhinus mrigala [ 24 ]. The LC 50 value of deltamethrin for 96 h treatment period in different fish species have been reported as follows: 2.6 μg/L for Brycon amazonicus [ 25 ], 4.7 μg/L for Salmo trutta fario (Brown trout) [ 26 ] and 15.47 μg/L for O. niloticus [ 27 ].…”
Section: Resultsmentioning
confidence: 99%